Characterization and Biochemical Assays of Streptomyces VanadiumDependent Chloroperoxidases - McKinnie, Shaun M.K. (Methods Enzymol, 2018)
Vanadium-dependent haloperoxidases (VHPOs) are fascinating enzymes that facilitate electrophilic halogen incorporation into electron-rich substrates, simply requiring vanadate, a halide source, and cosubstrate hydrogen peroxide for activity. Initially characterized in fungi and red algae, VHPOs were long believed to have limited regio-, chemo-, and enantioselectivity in the production of halogenated metabolites. However, the recent discovery of homologues in the biosynthetic gene clusters of the stereoselectively halogenated meroterpenoids from marine-derived Streptomyces bacteria has revised this paradigm. Their intriguing transformations have both enhanced and contributed to the fields of synthetic organic and natural product chemistry. We, herein, describe the expression, purification, and chemical assays of two characterized vanadium-dependent chloroperoxidase enzymes (NapH1 and Mcl24), and one homologue devoid of chlorination activity (NapH3), involved in the biosyntheses of halogenated meroterpenoid products.